Critical appraisal of the role of volumetric modulated arc therapy in the radiation therapy management of breast cancer - Cozzi, Luca; Lohr, Frank (Radiation oncology, 2017)
The aim of this review is the critical appraisal of the current use of volumetric modulated arc therapy for the radiation therapy management of breast cancer. Both clinical and treatment planning studies were investigated.